2021
DOI: 10.48550/arxiv.2110.09105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of two isomers of ethynyl cyclopentadiene in TMC-1: Abundances of CCH and CN derivatives of hydrocarbon cycles

J. Cernicharo,
M. Agundez,
R. I. Kaiser
et al.

Abstract: We report the detection of two isomers of ethynyl cyclopentadiene (c-C 5 H 5 CCH), namely 1-and 2-ethynyl-1,3-cyclopentadiene, in the direction of TMC-1. We derive column densities of (1.4±0.2)×10 12 cm −2 and (2.0±0.4)×10 12 cm −2 , respectively, for these two cyclopentadiene derivatives, which imply that they are about ten times less abundant than cyclopentadiene. We also report the tentative detection of ethynyl benzene (C 6 H 5 CCH), for which we estimate a column density of (2.5±0.4)×10 12 cm −2 . We deri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The recent results obtained towards TMC-1 with the Yebes 40m radio telescope through the QUIJOTE 1 line survey (Cernicharo et al 2021a) and those of the Green Bank 100m telescope with the GOTHAM survey (McGuire et al 2018) show that this source presents a paramount challenge to our understanding of the chemical processes in cold prestellar cores. Several cyclic molecules have been detected such as cyclopentadiene and indene (Cernicharo et al 2021b), as well as ortho-benzyne (Cernicharo et al 2021a), the cyano derivatives of cyclopentadiene, benzene, and naphthalene (McGuire et al 2018;McCarthy et al 2021;Lee et al 2021;McGuire et al 2021), and the ethynyl derivatives of cyclopentadiene (Cernicharo et al 2021c). Moreover, several extremely abundant hydrocarbons such as propargyl (Agúndez et al 2021), vinyl acetylene (Cernicharo et al 2021d), and allenyl acetylene (Cernicharo et al 2021e) have also been discovered towards TMC-1.…”
Section: Introductionmentioning
confidence: 99%
“…The recent results obtained towards TMC-1 with the Yebes 40m radio telescope through the QUIJOTE 1 line survey (Cernicharo et al 2021a) and those of the Green Bank 100m telescope with the GOTHAM survey (McGuire et al 2018) show that this source presents a paramount challenge to our understanding of the chemical processes in cold prestellar cores. Several cyclic molecules have been detected such as cyclopentadiene and indene (Cernicharo et al 2021b), as well as ortho-benzyne (Cernicharo et al 2021a), the cyano derivatives of cyclopentadiene, benzene, and naphthalene (McGuire et al 2018;McCarthy et al 2021;Lee et al 2021;McGuire et al 2021), and the ethynyl derivatives of cyclopentadiene (Cernicharo et al 2021c). Moreover, several extremely abundant hydrocarbons such as propargyl (Agúndez et al 2021), vinyl acetylene (Cernicharo et al 2021d), and allenyl acetylene (Cernicharo et al 2021e) have also been discovered towards TMC-1.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations of the molecular cloud TMC-1 with the Yebes 40m (Cernicharo et al, 2021a) and Green Bank (McGuire et al , 2018) radio telescopes have shown that this source presents a paramount challenge to our understanding of the chemical processes in cold prestellar cores. The detection of cyclopentadiene and indene (Cernicharo et al, 2021b), orthobenzyne (Cernicharo et al, 2021a), the cyano derivatives of cyclopentadiene, benzene and naphthalene (McGuire et al , 2018;McCarthy et al, 2021;Lee et al, 2021;McGuire et al , 2021), the ethynyl derivatives of cyclopentandiene (Cernicharo et al, 2021c), together with the discovery of extremely abundant hydrocarbons such as propargyl (Agúndez et al , 2021a), vinyl acetylene (Cernicharo et al, 2021d), and allenyl acetylene (Cernicharo et al, 2021e) suggest that key chemical processes involving hydrocarbons (radical, neutral, and/or ionic species) were not considered in previous chemical networks. Most of these species were not predicted to have a significant abundance.…”
Section: Introductionmentioning
confidence: 99%